Facial Synthesis of Adsorbent from Hemicelluloses for Cr(VI) Adsorption - Wei, Yi; Chen, Wei; Liu, Chuanfu; Wang, Huihui (Molecules (Basel, Switzerland), 2021)
It is challenging work to develop a low-cost, efficient, and environmentally friendly Cr(VI) adsorbent for waste water treatment. In this paper, we used hemicelluloses from chemical fiber factory waste as the raw material, and prepared two kinds of carbon materials by the green hydrothermal method as adsorbent for Cr(VI). The results showed that hemicelluloses hydrothermally treated with citric acid (HTC) presented spherical shapes, and hemicelluloses hydrothermally treated with ammonia solution (HTC-NH2) provided spongy structures. The adsorption capacity of the samples can be obtained by the Langmuir model, and the adsorption kinetics could be described by the pseudo-second-order model at pH 1.0. The maximum adsorption capacity of HTC-NH2 in the Langmuir model is 74.60 mg/g, much higher than that of HTC (61.25 mg/g). The green hydrothermal treatment of biomass with ammonia solution will provide a simple and feasible way to prepare adsorbent for Cr(VI) in waste water treatment.